2018
DOI: 10.3906/vet-1705-84
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sarcocystis spp. by polymerase chain reaction and microscopic examination in various beef products (minced meat, meatballs, fermented sausage)

Abstract: Sarcocystis species are the most commonly encountered parasitic organisms in animals. Sarcocystis hominis (Sarcocystis bovihominis), the species found in beef cattle, is not visible macroscopically in muscle tissue. In recent years it has been established that, in addition to being a zoonotic parasite transmitted via the consumption of beef, the parasite produces toxins and causes food poisoning. Therefore, this study was undertaken in order to determine the extent to which Sarcocystis species are present in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
2
2
0
1
Order By: Relevance
“…(92.2% of tissue samples with S. cruzi and 14% with S. hirsuta or S. hominis). These findings are in accordance to some investigations which have found in other countries: 100% in Brazil (23), 100% in Argentina (4), 100% in the United States (3), 97.4% in Belgium (24), 97.8% in Iraq (25) and 93.4% in Turkey (Iran border countries) (26). Whereas, the infection rate in the present study is considerable higher than Egypt, 7.45 (20), Malaysia, 36.2% (2), Philippines, 55% (27) and Ethiopia 82% (28).…”
Section: Discussionsupporting
confidence: 93%
“…(92.2% of tissue samples with S. cruzi and 14% with S. hirsuta or S. hominis). These findings are in accordance to some investigations which have found in other countries: 100% in Brazil (23), 100% in Argentina (4), 100% in the United States (3), 97.4% in Belgium (24), 97.8% in Iraq (25) and 93.4% in Turkey (Iran border countries) (26). Whereas, the infection rate in the present study is considerable higher than Egypt, 7.45 (20), Malaysia, 36.2% (2), Philippines, 55% (27) and Ethiopia 82% (28).…”
Section: Discussionsupporting
confidence: 93%
“…The PCR method is considered a valuable tool for identifying Sarcocystis alongside fundamental morphological methods to overcome the difficulties and erroneous results of the later [26]. Together with the gross examination, the 18S rRNA gene screening in the current study confirmed the identification of Sarcocystis sp.…”
Section: Discussionsupporting
confidence: 68%
“…As expected, Sarcocystis species were found in high prevalence in minced meat. Although there is no definite finding on S. hominis related to public health in our study, it is recommended that meat and meat products to be consumed be frozen in deep freeze for 1 day or cooked over 70°C for 8-15 minutes (20,37). Additionally, it is very important to control the disease in that the organs and tissues of the intermediate host should not be fed to cats or dogs raw or undercooked.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, it is thought that Turkish people consuming raw or undercooked beef products may have serious health problems. In addition, these studies have been mostly performed using conventional diagnostic methods (2,30,31,36,39,41), whereas there are only a limited number of molecular diagnostic studies in Turkey (12,20). Remarkably, the molecular characterization studies are insufficient in Turkey.…”
Section: Introductionmentioning
confidence: 99%